GENDER – BASED VIOLENCE IN CHIMAMANDA NGOZI ADICHIE’S PURPLE HIBISCUS - Osée, MUKASEREKA KHIKENZA (IJRDO - Journal of Social Science and Humanities Research, 2021)
Among the plagues surrounding the world today, the most crucial is Gender – based violence. Women and girls are subject of many atrocities, physically, morally and psychologically. Women’s body has become a weapon in battlefield.Women are wildly violated by all kinds of categories of men in society: soldiers, Statesmen, businessmen, etc… Teenagers are savagely violated and sometimes bear undesirable pregnancies which lead either to fistula or death during the birthday.Chimamanda Ngozi Adichie, the author of “Purple Hibiscus” is against the so – called fathers or chiefs of families who still practice domestic violence in maltreating their children and partners (wives).